2019
DOI: 10.1002/vms3.225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sequences and expression levels of genes related to follicular development and atresia between prolific and nonprolific goat breeds

Abstract: This study investigated the variations of the nucleotide sequences and ovarian expression levels of genes related to follicular development and atresia in prolific Jintang black goats and nonprolific Tibetan goats. Eight genes, FSHB, LHB, FSHR, LHCGR, ESR2, B4GANT2, BCL2 and BAX, were examined using reverse transcription‐polymerase chain reaction and quantitative real‐time PCR. The results showed that the nucleotide and deduced amino acid sequences of the LHB and BAX genes were not different, but there was one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In this case, the overexpression of B4GALNT2 in the ovary leads to atypical glycosylation of inhibin (inhibin is an important hormone that regulates ovarian function), which promotes high fecundity in sheep 54 . In addition, previous studies have shown that this gene is related to follicular development and atresia 55 . EEPD1 maintains the genome stability during embryonic replication stress by promoting homologous recombination (HR) and inhibiting non-homologous end joining (NHEJ) 56 .…”
Section: Resultsmentioning
confidence: 92%
“…In this case, the overexpression of B4GALNT2 in the ovary leads to atypical glycosylation of inhibin (inhibin is an important hormone that regulates ovarian function), which promotes high fecundity in sheep 54 . In addition, previous studies have shown that this gene is related to follicular development and atresia 55 . EEPD1 maintains the genome stability during embryonic replication stress by promoting homologous recombination (HR) and inhibiting non-homologous end joining (NHEJ) 56 .…”
Section: Resultsmentioning
confidence: 92%
“…follicular development, egg maturation, and hormonal regulation of endometrial development. It has been shown that the expression of genes responsible for follicular development and atresia differs in different goat breeds, and thus is genetically determined [21]. However, the results of other groups of scientists also highlight the influence of environmental conditions, such as husbandry, climate, and feeding, on the pregnancy rate [10].…”
Section: Resultsmentioning
confidence: 99%
“…Growth factors play an important role in the development and maintenance of follicles. Bone morphogenetic protein receptor 1B (BMPR-1B), bone morphogenetic protein 15 (BMP15), growth differentiation factor 9 (GDF9), and follicle-stimulating hormone β subunit (FSHB) are essential genes related to goat reproduction (Ghoreishi et al, 2019;Lan et al, 2003;Qi et al, 2019;Zi et al, 2020), and they are necessary growth factors in the ovary to initiate follicle development and regulate ovulation (Kumar et al, 2007). BMPR-1B affects the differentiation of granulosa cells and follicle development and can promote ovulation (Davis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%